Fabrication of Pb-Containing PtAu Nanoflowers via Galvanic Replacement Method for Electrocatalytical Oxidation of Methanol - Zhao Huang; Zhirou Zhang; Long Chao; Xueen Jia (Molecules)
A Pb-containing PtAu nanoflower electrocatalyst was deposited on the cathode via galvanic replacement reaction in a double-cabin galvanic cell (DCGC) with a Cu plate as the anode, a multiwalled carbon nanotube (MWCNT) modified glassy carbon electrode (GCE) as the cathode, 0.1 M HClO4 aqueous solution as the anolyte, and Pb2+-containing Pt4+ salt and Au3+ salt mixed aqueous solution as the catholyte, respectively, and the electrocatalytic performance of the modified electrode toward methanol oxidation in the alkaline medium was investigated. Electrochemical studies reveal that the stripping of bulk Cu can induce underpotential deposition (UPD) of Pb on Pt during the galvanic replacement reaction, which affects the morphology and composition of Pb-containing PtAu nanoparticles. Under the optimal experimental conditions, a Pb-Pt3Au1/MWCNTs/GCE shows the highest activity and the best stability toward electrocatalytic oxidation of methanol in the alkaline medium, and the Pt active area-normalized specific electrocatalytic activity of Pb-Pt3Au1/MWCNTs/GCE is as high as 59.8 mA cmPt−2. We believe that the method presented here of depositing highly active noble metal nanostructures by galvanic replacement reaction in a DCGC device is expected to be widely applied in the preparation of nanomaterials for their study in fuel cells and electrocatalysis.